(untitled) (Journal of the College of Basic Education, 2022)
The style in the plastic arts is subject to study and research as it is one of the most important topics that enable us to know and study the stylistic structure and the graphic path of the artist’s development through analyzing the artwork, and because the style is one of the technical characteristics of any artistic production, as through it the artist’s artistic identity becomes clear from the mechanism he presents in showing the work. artistic. The research included a study of the stylistic structure of the artist, Qasim Hamzah, and an attempt to discover the path of the graphic line of the elements that define his artistic style.